Principles of Islamic counselling and psychotherapy - Ahmad Sudan, Salmi (Leena and Luna International Co Ltd., 2017)
Counselling and psychotherapy are parts of the modern discipline of psychology related to the study of human mind and behaviour. Islamic counselling is a method to infuse values and spirituality into the process of therapy and treatment as well as to overcome various difficulties through religious teachings which will in turn help in balancing the physical and the spiritual needs of an individual. To avoid failures, it is crucial to accomplish a balanced life; as spirituality creates inner peace. Therefore, the main sources of Islamic counselling are the Qur’an, the book of God and the hadith of the Prophet. Both of these sources emphasise on the well-being, satisfaction and the salvation of the individual. During the medieval period, extensive study on human psychology had been undertook by Muslim scholars such as Al-Razi, Ibn Sina, Al-Balkhi, and Al-Ghazali. These scholars have laid the foundations and principles of Islamic counselling. Some of the key principles of Islamic counselling are: confidentiality, autonomy, beneficence, justice, motivation, multicultural counselling, and personality development. It is important to relate that spirituality has its own coping strategies